Effect of particulate matter 2.5 on gene expression profile and cell signaling in JEG‐3 human placenta cells. Issue 11 (5th July 2018) - Kim, Woong; Cho, Yoon; Song, Mi‐Kyung; Lim, Jung‐hee; Kim, Jin young; Gye, Myung Chan; Ryu, Jae‐Chun
Abstract : Particulate matter the environmental toxicant, with a diameter less than or equal to 2.5 μm (PM2.5 ) is a common cause of several respiratory diseases. In recent years, several studies have suggested that PM2.5 can influence diverse diseases, such as respiratory diseases, cardiovascular diseases, metabolic diseases, dementia, and female reproductive disorders, and unhealthy birth outcomes. In addition, several epidemiological studies have reported that adverse health effects of PM2.5 can differ depending on regional variations. In the present study, to evaluate specific adverse health effects of PM2.5, we collected two different PM2.5 samples from an underground parking lot and ambient air, and we evaluated cytotoxicity with eight different cell lines originating from human organs. Then, we selected JEG‐3 human placenta cells, which show high cytotoxicity to both PM samples. Through RNA sequencing, gene expression profiling, and a gene ontology (GO) analysis of JEG‐3 after exposure to two different PM2.5 samples, we identified 1021 commonly expressed genes involved in immune responses, the regulation of apoptosis, and so forth, which are known to induce several adverse health effects. In addition, we identified genes related to the calcium‐signaling pathway, steroid hormone biosynthesis, and the cytokine‐cytokine receptor interaction through a Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Then, we confirmed these gene expressions using qRT‐PCR, and the protein levels of mitogen‐activated protein kinases and COX‐2 with progesterone decreased using western blotting and enzyme‐linked immunosorbent assay. In conclusion, this study suggests the possible toxic mechanism of human placenta that might be associated with PM2.5 ‐induced female reproductive disorders.